Review of Gavin Bryars: The Sinking of the Titanic; Jesus’ Blood Never Failed Me Yet, Christopher Hobbs; John Adams; Gavin Bryars: Ensemble Pieces, Brian Eno: Discreet Music, and David Toop; Max Eastley: New and Rediscovered Musical Instruments - Roberts, David (Contact: A Journal for Contemporary Music (1971-1990), 1976)